Adsorption of Phthalates on Municipal Activated Sludge - Hongbo Wang; Haining Li; Qicheng Song; Lili Gao; Ning Wang (Journal of Chemistry)
Phthalates (PAEs) are commonly detected in discharge of municipal wastewater treatment plants. This study investigated the removal of six typical PAEs with activated sludge and the results revealed that concentrations of aqueous PAEs decreased rapidly during the beginning 15 min and reached equilibrium within 2 hours due to the adsorption of activated sludge. The process followed first-order kinetic equation, except for dioctyl phthalate (DOP). The factors influencing the adsorption were also evaluated and it was found that higher initial concentrations of PAEs enhanced the removal but affected little the adsorption equilibrium time. The adsorption of PAEs favored lower operating temperature (the optimum temperature was approximately 25°C in this research), which could be an exothermic process. Additionally, lower aqueous pH could also benefit the adsorption.